Association between the risk of relative energy deficiency in sport and cholesterol levels in Finnish endurance athletes - Silvennoinen, Julia I. K.; Sipilä, Pyry N.; Valtonen, Maarit; Mjøsund, Katja; Kinnula, Ville; Hirvelä, Leon; Mierlahti, Laura; Ihalainen, Johanna K. (BMJ, 2026)
Background
Relative energy deficiency in sport (REDs) is a condition caused by chronic and/or severe low energy availability. Endurance athletes are at risk of REDs, which are characterised by negative effects on health and performance. Disturbed cholesterol metabolism is a suggested indicator of REDs and could affect the future cardiovascular health of athletes. We investigated the association between the REDs risk and cholesterol levels in endurance athletes.
Methods
Finnish endurance athletes (n=87; female 44, male 43) were recruited as part of the Athletic Performance and Nutrition study. The participants were examined at the beginning (T1) and end (T2) of the training season. The REDs risk was assessed using the REDs Clinical Assessment Tool version 2.
Results
At T1, 37 (77%) female and 31 (72%) male athletes were at medium-to-high REDs risk. The REDs risk was not associated with cholesterol levels in a cross-sectional analysis, and no overall change in the REDs risk or the cholesterol levels was observed between T1 and T2. In female athletes, an increase in REDs risk status from low to medium-to-high between T1 and T2 was associated with a decrease in low-density lipoprotein (LDL) cholesterol (beta adjusted for age −0.62, 95% CI −0.94 to −0.30) and total cholesterol (beta adjusted for age −0.85, −1.42 to −0.28)).
Conclusions
REDs risk was not associated with cholesterol levels at T1 or T2. However, in female athletes, an increase in the REDs risk across time points was associated with a decrease in LDL and total cholesterol levels.